Analisis Siklis Terhadap Kegiatan Penjualan Gula Aren Pada Usaha Mikro Di Kabupaten Lebak - Iwan Ridwan; Ferdian Arie Bowo; Abdurozak . (E-Journal Studia Manajemen, 2012)
This study motivated by differences sales activities at micro palm sugar in Kampung Desa Cibuluh Mugijaya Cigemblong Lebak caused by the different circumstances use of palm sugar. The purpose of this study was to determine effect of cyclical on sales activities micro palm sugar. This study uses qualitative descriptive method. Informants in this study were middlemen palm sugar as many as 5 people. The results showed that cyclical has an effect on sales activity.